Deep structure of the Obolon astrobleme according to the results of spatial integral seismic-gravity modeling - T. Fedchenko; Yu. Anishchenko; N. Ganzhenko; A. Petrovsky (Геофизический журнал, 2015)
Spatial seismic-gravity modeling of the deep geological structure within the Obolon depression has been done. Modeling results confirm the validity of assumption that depression has been formed as an impact structure. Features of the rock density distribution within the crystalline basement allowed to specify its tectonic structure and mineral composition and also to determine a probable location of the two parts of meteoritic object.